Dead & Buried - Sherman, Gary.; Redfield, Dennis; Jack Albertson; Lisa Blount; Melody Anderson; Nancy Locke; Robert Englund; James Farentino (USA Blue Underground, 1981)
Potters Bluff, Rhode Island. may seem to be a sleepy little town. At least for the casual visitor and the local sheriff, Daniel Gillis. However, all of a sudden, there are a lot of strange murders where strangers or people passing through are killed by mobs of townspeople. Only Sheriff Gillis has no clue to what's going on. Fortunately, the town has an excellent undertaker, William G. Dobbs, who is happy to take care of this sudden death-wave which is good for his business. Gillis soon discovers clues that lead to many of the local inhabitants involved in the killings, including his own wife Janet.
A suspense horror film set in a small coastal town where, after a series of gory murders commited by mobs of townspeople against visiting tourists, the corpses begin to come back to life.
Jeff Millar
Languages: English Subtitles: English
Keywords: Horror; SciFi